Viscosity Behaviour of Cryptand C222 in Methanol Solution - ABDUL-RAZZAK, B.I.; AL-NOZILI, MOHAMED (Asian Journal of Chemistry, 2010)
The viscosity measurements for potassium chloride solution contaning C222 in methanol at 25°C have been investigated. The relative viscosity in the studied concentration range was found to fit well with Jones-Dole and Falkenhagen equation. The results are interpreted in terms of molecular interaction and occuption of cryptand cavity by methanol molecules.